O ensino de inglês em uma escola pública municipal do oeste paranaense: um estudo de caso etnográfico. - Sabadin, Marlene Neri (2006)
This research was carried out in a West city of Paraná State. Its goal was to analyze the introduction of English as a Foreign Language for children in elementary school. To reach this goal some classes had been recorded and analyzed in order to describe the teacher-student interaction and the activities in the classroom. Besides that some interviews had been done with the principal and the teacher of English as a way to collect information about the curriculum, language teaching planning and the school facilities to improve the English learning process. For this reason it was used ethnographic microanalysis as classes observation, field diaries and research of other educational documents. To analyze the data collected in the English Language classic authors had been read to accomplish the research and to comprehend the data. It was noticed that the quantity of input during the English class had been scarce, characteristic very similar to English classes to teenager students, from 5th grade to 8th grade, since teacher have not good fluency in English, then they use to teach through grammar and translation activities with some drills. It was very productive if teachers could improve their own languages abilities, even oral ability, by English courses provided by the University. These courses might pre service or in service in order to prepare teachers to face this new challenge teach English for kids.